Endocannabinoid tone is higher in healthy lean South Asian than white Caucasian men - Vasudev Kantae (Nature Portfolio, 2017)
Abstract South Asians have a higher risk to develop obesity and related disorders compared to white Caucasians. This is likely in part due to their lower resting energy expenditure (REE) as related with less energy-combusting brown adipose tissue (BAT). Since overactivation of the endocannabinoid system is associated with obesity and low BAT activity, we hypothesized that South Asians have a higher endocannabinoid tone. Healthy lean white Caucasian (n = 10) and South Asian (n = 10) men were cold-exposed to activate BAT. Before and after cooling, REE was assessed and plasma was collected for analysis of endocannabinoids and lipids. At thermoneutrality, South Asians had higher plasma levels of 2-arachidonoylglycerol (2-AG; 11.36 vs 8.19 pmol/mL, p < 0.05), N-arachidonylethanolamine (AEA; 1.04 vs 0.89 pmol/mL, p = 0.05) and arachidonic acid (AA; 23.24 vs 18.22 nmol/mL, p < 0.001). After pooling of both ethnicities, plasma 2-AG but not AEA positively correlated with triglycerides (R2 = 0.32, p < 0.05) and body fat percentage (R2 = 0.18, p < 0.05). Interestingly, AA negative correlated with REE (R2 = 0.46, p < 0.001) and positively with body fat percentage (R2 = 0.33, p < 0.01). Cooling increased endocannabinoids. In conclusion, South Asian compared to white Caucasian men have higher endocannabinoid tone. This suggests that endocannabinoids may, at least in part, underlie the disadvantageous metabolic phenotype of South Asians later in life.